The shifting dynamics of great power competition - Masuda, Masayuki (NIDS, 2023)
The Shifting Dynamics of Great Power Competition examines the logic and structure of intensifying strategic competition between the United States and China, as well as the role of the Russia factor in Part I. Part II of the book discusses how the great power competition, with a focus on the U.S.-China rivalry, has extended to other countries and regions